IDENTIFIKASI KERAGAMAN DAN DOMINASI GULMA BEBERAPA TANAMAN PANGAN DAN HORTIKULTURA PADA FASE VEGETATIF - Dianawati; Danar Hadisugelar; Yenny Amilda; Yenni Marnita; Saiful Mahdi (University of Prof. Dr. Hazairin, SH, 2025)
This study aimed to identify the types, diversity, and dominance of weeds found under several food and horticultural crops during the vegetative phase, namely eggplant, peanut, soybean, and chili. The research was conducted at the educational field of Samudra University using a quadrat method measuring 1 × 1 m with three replications. The identification results showed that Cyperus rotundus appeared in almost all locations and became the dominant weed in several plots. The Shannon-Wiener diversity index (H’) ranged from 0.46 to 1.49, indicating a low to moderate level of diversity, while the evenness index (J’) ranged from 0.67 to 0.92, suggesting that the distribution of individuals among species was fairly even. The highest dominance was recorded for Cyperus rotundus in soybean fields and Spermacoce alata in chili fields. These findings highlight the need for specific control strategies targeting dominant weeds according to crop type to maintain crop productivity.